Pengaruh Simulasi Awal Waktu Pengamatan Terhadap Hasil Prediksi Pasang Surut Di Perairan Kotabaru Menggunakan Metode Admiralty - Handika, Syusella Kalvi; Hendri, Andy; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
This study examines variations in the initial time of observation based on the Hijri calendar which aims to determine the most accurate time to make observations in the field. The analysis of this research used the Admiralty method with hourly observation data for 15 days. The data uses tide data in Kotabaru waters and simulated against two hundred and forty-three time variations. The results of the data analysis show that the smallest average root mean square error (RMSE) resulting from the 15-day tide prediction is 16.68 cm, which is the prediction of the start date of the 16 Hijri calendar. So that the most appropriate time to make tidal observations in the field for tidal predictions in Kotabaru waters is on the 16th of each Hijri month or during the fourth moon phase (humpback month). The value of the formzhal number obtained is 0.66, so the tidal type in the study location is included in the semi-diurnal tide type classification.Key words: beginning time, admiralty method, RMSE.